PROMOTING ISLAMIC-INTEGRATED MATHEMATICS PROBLEM-SOLVING TO ENHANCE STUDENTS' CONCEPTUAL UNDERSTANDING IN MADRASAH - Mastuti, Ajeng Gelora; Sehuwaky, Nurlaila; Nuru, Zumrotin (Universitas Labuhanbatu, 2024)
This study investigates the impact of Islamic-integrated mathematics problem-solving on students' conceptual understanding in madrasah settings. Using a mixed-methods approach with 60 students from MAN 1 Maluku Tengah, the research employed experimental and control groups to compare learning outcomes between Islamic-integrated and conventional mathematics problems. Data were collected through conceptual understanding tests, student perception surveys, and teacher interviews. Results revealed a significant difference in mathematical conceptual understanding between groups (p = 0.008), with the experimental group achieving a higher mean score (75.20) compared to the control group (68.90). Qualitative analysis identified distinct problem-solving approaches among students, with strong performance in translation and interpretation stages but challenges in extrapolation. Student perceptions were predominantly positive, with increased interest in mathematics when integrated with Islamic values, despite 45% having no prior exposure to such integration. The findings suggest that Islamic-integrated mathematics education enhances conceptual understanding while highlighting the need for additional support in developing higher-order thinking skills. This research contributes to the growing body of knowledge on culturally responsive mathematics education in Islamic contexts.